Metal-Organic Framework in Pharmaceutical Drug Delivery - Kundu, Sudipto; Swaroop, Akey K.; Selvaraj, Jubie (Current Topics in Medicinal Chemistry, 2023)
Metal-organic frameworks (MOFs) are porous, crystalline materials made up of organic ligands and metal ions/metal clusters linked by coordinative bonds. This large family is becoming increasingly popular for drug delivery due to their tuneable porosity, chemical composition, size and shape, and ease of surface functionalization. There has been a growing interest over the last decades in the design of engineered MOFs with controlled sizes for a variety of biomedical applications. Starting with the MOFs classification adapted for drug delivery systems (DDSs) based on the types of constituting metals and ligands. MOFs are appealing drug delivery vehicles because of their substantial drug absorption capacity and slow-release processes, which protect and convey sensitive drug molecules to target areas. Other guest materials have been incorporated into MOFs to create MOF-composite materials, which have added additional functionalities such as externally triggered drug release, improved pharmacokinetics, and diagnostic aids. Magnetic nanoparticles in MOFs for MRI image contrast and polymer coatings that increase blood circulation time are examples of synthetically adaptable MOF-composites. By including photosensitizers, which exert lethal effects on cancer cells by converting tumour oxygen into reactive singlet oxygen (1O2), metalorganic frameworks have been employed for photodynamic treatment (PDT) of malignancies among a multitude of nanosized therapies. Importantly, a variety of representative MOF applications are described from the perspectives of pharmaceutics, disease therapy, and advanced drug delivery systems. However, because of their weak conductivity, selectivity, and lack of modification sites, MOF materials' uses in electrochemical biosensing are restricted. MOF-based composites provide excellent electrical conductivity and robust catalytic activity by adding functionalized nanoparticles into MOF structures, which process benefits over single component MOFs.
Keywords: Metal organic framework